The projection of mean temperature and precipitation for Ethiopia, Banglandesh, and Netherlands - Aydın, Gamze. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Climate change is an important problem for today and it will also continue to be an important problem for the future. The purpose of this thesis is to analyze the future of the climate through climate modelling in 3 countries which are geographically signi - cant, namely Ethiopia, Bangladesh and the Netherlands. First of all, we simulated todays climate for the years between 1970 {u100000} 2000 by using RegCM 4:3:5:5 which is the regional climate modelling for analysis of regional climate change. We used ECHAM5, which is the atmospheric global climate model, as the forcing data when making this simulation and analyzed average surface temperature and precipitation variables. We compared model simulation for 1970 {u100000} 2000 obtained by using RegCM 4:3:5:5 with the data from CRU which is the observational station data to examine correctness of our model. As a result, it was concluded that geographical features, climate events and topography have a signi - cant e ect in climate modelling as well. Di erences which occurred especially in modelling average precipitation volume indicated us that it is more di cult to model precipitation than temperature. Following the veri cation of todays data for Ethiopia, Bangladesh and the Netherlands, data of ECHAM5 A1B scenario was used and thus seasonal average surface temperature and precipitation values obtained for the climate model for the years of 2020 - 2050 being the future time by using RegCM 4:3:5:5: As a result of comparison of todays and futures data, it was found that considerable increases will occur in temperature between the years of 2020 - 2050:.
Keywords: Precipitation (Meteorology) -- Ethiopia.; Precipitation (Meteorology) -- Banglandesh.; Precipitation (Meteorology) -- Netherlands.; Atmospheric temperature -- Ethiopia.; Atmospheric temperature -- Banglandesh.; Atmospheric temperature -- Netherlands.